Crustal thickness and velocity structure of Malay Peninsula inferred from joint inversion of receiver functions and surface waves dispersion - Abdul Latiff, A.H. (2019)
The Malay Peninsula is located within the Sunda shelf that is subdivided geologically into three distinctive tectonic belts; western, central and eastern belts. The north-south orientation of these belts was formed during the Paleo-Tethys subduction process in the Late Paleozoic. Bentong-Raub suture zone separates the central and western belts. While extensive studies have been conducted at the surface and near surface scale, the subsurface model of the Earth's crust and upper mantle layers within this region are relatively few. Crustal structure model is crucial in investigating the cause of local earthquakes, which shocked Peninsular Malaysia between 2007 and 2009. The present study is conducted adopting the joint inversion of the P-wave receiver functions and surface wave dispersions techniques using the data collected from eight Seismological stations in the Malay Peninsula. The receiver function for each station was computed using over a thousand tele-seismic earthquake waveforms, recorded by the three-component broadband seismometers. For each station, the H-k was used to determine the Vp/Vs ratio and the depth to the Moho. This step was conducted to have an initial constraint for the crustal thickness. For the surface wave dispersion calculations, on the other hand, two hundred local and regional earthquakes with focal depth less than 30 km and with magnitudes mb 6.0 and above that occurred along South-East Asia's ring of fire were analyzed. The analyses obtained from these two techniques were jointly inverted through a two-phases of velocity inversion to determine the 1-D velocity profile for each station. The results of inversion indicate that the Moho boundary is getting shallower towards the north of Malay Peninsula, as a 26 km depth of crust-mantle boundary were determined in station SKLT south Thailand. Furthermore, the subsurface profile of the western belt of Malay Peninsula was also found to be highly complicated, with complex receiver function responses being computed beneath the IPM and KUM stations where slow velocity zones are identified within the 10â20 km crustal depth. The region in southern Thailand might also have originated from Indochina/East Malaya block, due to similar crustal velocity characteristics found beneath the region compared to the area beneath KOM, JRM and BTDF stations in the southern part of Malay Peninsula and Singapore. The Vp/Vs ratios for the crust indicate that the crust is generally undisturbed except for station SKLT south Thailand. This may indicate that the occurrence of a large earthquake in the region is not likely. Â© 2018 Elsevier Ltd